Successful Renal Transplantation of Deceased Donor Kidneys With 100% Glomerular Fibrin Thrombi and Acute Renal Failure Due to Disseminated Intravascular Coagulation. Issue 6 (June 2017) - Soares, Kevin C.; Arend, Lois J.; Lonze, Bonnie E.; Desai, Niraj M.; Alachkar, Nada; Naqvi, Fizza; Montgomery, Robert A.
Abstract : Background: Disseminated intravascular coagulation (DIC)-positive kidneys have historically been turned down for fear of poor outcomes. Higher severity injuries, which are prone to DIC, are typically seen in younger, otherwise healthy potential donors. The continued kidney allograft shortage has generated interest in the use of these DIC-positive grafts. There have been some reports of acceptable outcomes of renal transplantation using kidneys from donors with DIC. There are multiple clinical series demonstrating good outcomes from DIC-positive kidneys when the extent of glomeruli containing fibrin thrombi is less than 50% and donor renal function is preserved. These grafts are frequently associated with a period of delayed graft function. Methods: We report 2 transplants with kidneys from brain dead donors with known DIC. Results: Both donors had renal failure and pretransplant renal biopsies showing 100% of the glomeruli containing fibrin thrombi. The recipients experienced delayed graft function requiring hemodialysis which was discontinued on postoperative days 18 and 39 for cases 1 and 2, respectively. Both patients are now over 14 months posttransplant with stable allograft function. Conclusions: Until clearer organ selection criteria are established, caution should be exercised when considering the use of kidneys with a similar phenotype and allocation decisions made by a multidisciplinary transplant team on a case-by-case basis. Abstract : Two renal transplant patients receive grafts from donor with known DIC and are now over 14 months posttransplant with stable allograft function, but allocation decisions are made by a multidisciplinary transplant team on a case-by-case basis until clearer organ selection criteria are established.